Be Fit Bye Fat Sebagai Metode Peningkatan Derajat Kebugaran Jasmani Pegawai Pertamina MOR IV Semarang - Irawan, Fajar Awang; Romadhoni, Syahru; Permana, Dhias Fajar Widya; Billah, Tafriyadhur Risa; Hadi, Hadi (Fakultas Ilmu Olahraga, Universitas Negeri Surabaya, 2021)
The purpose of this study was to find out the degree of physical fitness and increase knowledge about the management of physical activity and healthy diet through methods to reduce obesity and overweight rates of Pertamina MOR IV Semarang employees. The method of implementation of this research is Pretest posttest experiment . The total participants were 44 Pertamina MOR IV Semarang internal employees and willing to be participants in this research was shown by completing the willingness sheet to be a participant. The instruments used are a measurement of body mass index (BMI) and physical fitness and exercise assistance. The results of this study overview found that employees experienced an increase of 41 employees (93.18 %) while that did not increase by 3 Employees (6.82 %). the results showed that there was an increase in the ercentage rate of physical fitness degree and a significant increase in strength levels compared to the decrease through the program